Patient reported outcome measures: The impact of environment on VHI‐10 responses. Issue 1 (30th January 2023) - Kinberg, Eliezer C.; Taree, Amir; Gray, Mingyang; Filip, Peter; Courey, Mark
Abstract: Objective: A key outcome measure in the clinical evaluation of dysphonia is the Voice Handicap Index (VHI‐10). The clinical validity of the VHI‐10 was established from surveys administered in the physician's office. We aim to understand whether VHI‐10 responses remain reliable when the questionnaire is completed in settings other than the physician's office. Methods: This is a prospective observational study conducted over a 3‐month period in the outpatient laryngology setting. Thirty‐five adult patients presenting with a complaint of dysphonia, which was symptomatically stable for the preceding 3 months, were identified. Each patient completed a VHI‐10 survey during the initial office visit, followed by three weekly out‐of‐office (termed "ambulatory") VHI‐10 surveys, over the course of 12 weeks. The specific setting in which the patient completed the survey was recorded (social, home, or work). The Minimal Clinically Important Difference (MCID) is defined as 6 points based on existing literature. T‐tests and a test of one proportion were used for analysis. Results: A total of 553 responses were collected. Of these, 347 ambulatory scores (63%) differed from the Office score by at least the MCID. Specifically, 94 (27%) were higher than the in‐office score by 6 or more points while 253 (73%) were lower. Conclusion: The setting in which the VHI‐10 is completed affects how the patient answers the questions. The score is dynamic, reflecting effects of the patients' environment during completion. Utilization of VHI‐10 scores to measure clinical treatment response is only valid if each response is obtained in the same setting. Level of Evidence: 4 Abstract :